2018
DOI: 10.3389/fgene.2018.00338
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FMR1 Premutation on Neurobehavior and Bioenergetics in Young Monozygotic Twins

Abstract: Mitochondrial dysfunction (MD) has been identified in lymphocytes, fibroblasts and brain samples from adults carrying a 55–200 CGG expansion in the fragile X mental retardation 1 (FMR1) gene (premutation; PM); however, limited data are available on the bioenergetics of pediatric carriers. Here we discuss a case report of three PM carriers: two monozygotic twins (aged 8 years) harboring an FMR1 allele with 150–180 CGG repeats, with no cognitive or intellectual issues but diagnosed with depression, mood instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
(77 reference statements)
3
12
3
Order By: Relevance
“…Mitochondrial dysfunction has been reported not only in neurodegeneration (Friedland et al, 1983;Minoshima et al, 1997;Chiaravalloti et al, 2015) but also in pre-symptomatic, genetically-susceptible individuals (Small et al, 1995;Reiman et al, 1996;Mosconi et al, 2006;Ossenkoppele et al, 2013). In line with these studies and our previous reports on the PM (Napoli et al, 2016a(Napoli et al, , 2018, our study strongly indicates that global impairment of bioenergetics, and likely the subsequent energy depletion, is one of the earliest functional changes prior to the onset of overt clinical symptoms. This is supported by the relatively milder mitochondrial dysfunction in PM carriers without FXTAS and FXPOI which is enhanced with the diagnosis and progression of FXTAS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mitochondrial dysfunction has been reported not only in neurodegeneration (Friedland et al, 1983;Minoshima et al, 1997;Chiaravalloti et al, 2015) but also in pre-symptomatic, genetically-susceptible individuals (Small et al, 1995;Reiman et al, 1996;Mosconi et al, 2006;Ossenkoppele et al, 2013). In line with these studies and our previous reports on the PM (Napoli et al, 2016a(Napoli et al, , 2018, our study strongly indicates that global impairment of bioenergetics, and likely the subsequent energy depletion, is one of the earliest functional changes prior to the onset of overt clinical symptoms. This is supported by the relatively milder mitochondrial dysfunction in PM carriers without FXTAS and FXPOI which is enhanced with the diagnosis and progression of FXTAS.…”
Section: Discussionsupporting
confidence: 90%
“…Our team was the first to report mitochondrial dysfunction as a common feature in biological samples from PM carriers (Napoli et al, 2013(Napoli et al, , 2016a(Napoli et al, ,b, 2018Song et al, 2016) as well as in murine models of the PM (Napoli et al, 2016a). This decreased mitochondrial bioenergetics is present in PM carriers with and without FXTAS and even in some pediatric carriers (Napoli et al, 2018). However, to our knowledge, no study has to date characterized the metabolic footprint of the PM and related clinical and cognitive features in female carriers of the PM.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Abundant Proteins and Fragile X-Associated Tremor/Ataxia Syndrome-Associated Dysfunction, mRNA, and Proteins Surprisingly, we did not identify differential abundance of mitochondrial proteins or those associated with mitochondrial dysfunction in FXTAS cortexes. Despite the evidence demonstrating altered mitochondrial dysfunction and decreased mitochondrial protein expression in PM subjects (Ross-Inta et al, 2010;Napoli et al, 2016Napoli et al, , 2018, dysfunction was not found in association with our DAPs in late-stage FXTAS. This may be the result of late-stage disease progression and the overall cellular abundance of proteins outweighing those specifically associated with mitochondria.…”
Section: Correlation Between Differentiallycontrasting
confidence: 91%
“…FMR1 -related measures, including CGG repeat number, percent of methylation, FMR1 mRNA and FMRP expression levels have been correlated to neurocognitive and social–affective functioning assessments and mental health problems in individuals with FXS [30,31,32,33,34,35,36,37,38]. The magnitude of the observed correlations generally suggests that these molecular biomarkers are likely accounting only for a proportion of the phenotypic variability of this disorder.…”
Section: Fmr1 Molecular Measuresmentioning
confidence: 99%